Assessing the efficacy of treatments for digital dermatitis in organic dairy systems - Paudyal, Sushil, author; Pinedo, Pablo, author (Colorado State University. Libraries, 2017)
Digital dermatitis is a major cause of lameness in dairy cows causing pain in the limbs leading to reduced animal welfare and significant economic loss. With strict antibiotic regulations and increasing organic dairies, the clinically validated non-antibiotic treatment options are of great value. The objective of the study was to evaluate the efficacy of treatment of digital dermatitis using different combinations of copper sulfate, iodine, and honey. Cows with M1 and M2 DD lesion score were identified and enrolled in the hoof-trimming chute. Cows were randomized to be treated with one of the three treatment options: Copper sulfate and Iodine (CS-I), Honey and Iodine (HO-I) and Control (CON). All 70 cows were followed up on D3, D12 and D28 and a subsample of 45 cows were followed until d120 to evaluate lesion size, lesion stage, lameness score and pain response. Tissue samples were collected on D3, D28 and D120 to investigate dynamics of microbial metagenomics. The data were analyzed in SAS using PROC MIXED and PROC GENMOD with repeated measures. The results show that 43% of the lesions were found on the left feet and 57% on the right feet. The early erosive form of lesions changes into papillomatous mature form as the lesion progresses irrespective of treatment application. The lesion size differed among treatment groups and the effect varied with different follow-up days (P< 0.05). The lesion decreased for both CS-I and HO-I group till day 12 after which the HO-I group had an increase in lesion size. In contrast to this CON group had a slower decrease in lesion size. The pain response was decreased for CS-I and less for HO-I groups. The odds of pain and the odds of getting a lame cow decreases as the time progresses. Thus, non-antibiotic treatment options are effective in controlling pain and decreasing lesion size up to 12 days. Also, clinical assessment of animals and evaluation of lesions suggest CS-I combination is superior to HO-I and CON group.
230 - Sushil Paudyal
Keywords: dairy; digital dermatitis